Multivariable normal tissue complication probability model-based treatment plan optimization for grade 2–4 dysphagia and tube feeding dependence in head and neck radiotherapy. Issue 3 (December 2016) - Kierkels, Roel G.J.; Wopken, Kim; Visser, Ruurd; Korevaar, Erik W.; van der Schaaf, Arjen; Bijl, Hendrik P.; Langendijk, Johannes A.
Abstract: Background and purpose: Radiotherapy of the head and neck is challenged by the relatively large number of organs-at-risk close to the tumor. Biologically-oriented objective functions (OF) could optimally distribute the dose among the organs-at-risk. We aimed to explore OFs based on multivariable normal tissue complication probability (NTCP) models for grade 2–4 dysphagia (DYS) and tube feeding dependence (TFD). Materials and methods: One hundred head and neck cancer patients were studied. Additional to the clinical plan, two more plans (an OFDYS and OFTFD -plan) were optimized per patient. The NTCP models included up to four dose–volume parameters and other non-dosimetric factors. A fully automatic plan optimization framework was used to optimize the OFNTCP -based plans. Results: All OFNTCP -based plans were reviewed and classified as clinically acceptable. On average, the Δdose and ΔNTCP were small comparing the OFDYS -plan, OFTFD -plan, and clinical plan. For 5% of patients NTCPTFD reduced >5% using OFTFD -based planning compared to the OFDYS -plans. Conclusions: Plan optimization using NTCPDYS - and NTCPTFD -based objective functions resulted in clinically acceptable plans. For patients with considerable risk factors of TFD, the OFTFD steered the optimizer to dose distributions which directly led to slightly lower predicted NTCPTFD values as compared to the other studied plans.